2021
DOI: 10.3390/antiox10111738
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Administration in Fe–S Cluster Homeostasis

Abstract: Mitochondria are the key organelles of Fe–S cluster synthesis. They contain the enzyme cysteine desulfurase, a scaffold protein, iron and electron donors, and specific chaperons all required for the formation of Fe–S clusters. The newly formed cluster can be utilized by mitochondrial Fe–S protein synthesis or undergo further transformation. Mitochondrial Fe–S cluster biogenesis components are required in the cytosolic iron–sulfur cluster assembly machinery for cytosolic and nuclear cluster supplies. Clusters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 220 publications
(351 reference statements)
0
18
0
Order By: Relevance
“…The acid-labile sulfur, including Fe-S clusters, is sulfide [ 52 , 53 ]. When O 2 •− and HO• oxidize Fe-S clusters and release Fe 2+ [ 54 , 55 , 56 ], the sulfur in the cluster is theoretically oxidized to sulfane sulfur (zero valences), as sulfide reacts with ROS to produce sulfane sulfur [ 57 ]. H 2 O 2 and tBH were unable to increase iSS ( Figure 7 A), perhaps partly because they are rapidly metabolized by E. coli cells [ 58 ], partly because they react with sulfane sulfur at a relatively slow rate [ 40 ], and partly because they do not directly damage Fe-S clusters [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acid-labile sulfur, including Fe-S clusters, is sulfide [ 52 , 53 ]. When O 2 •− and HO• oxidize Fe-S clusters and release Fe 2+ [ 54 , 55 , 56 ], the sulfur in the cluster is theoretically oxidized to sulfane sulfur (zero valences), as sulfide reacts with ROS to produce sulfane sulfur [ 57 ]. H 2 O 2 and tBH were unable to increase iSS ( Figure 7 A), perhaps partly because they are rapidly metabolized by E. coli cells [ 58 ], partly because they react with sulfane sulfur at a relatively slow rate [ 40 ], and partly because they do not directly damage Fe-S clusters [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial sulfurtransferases, TST and MPST, participate in the formation of iron-sulfur (Fe-S) clusters [ 23 ]. Both enzymes, which are highly expressed in AML (MOLM-14, MV4-11) as well as B-ALL (REH) cells, may therefore play an important role in the formation of Fe-S clusters that are components of the respiratory chain complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfurtransferases (thiosulfate sulfurtransferase, TST, rhodanese; 3-mercaptopyruvate sulfurtransferase, MPST; gamma-cystathionase, CTH) and cystathionine beta-synthase (CBS) are involved in l -cysteine metabolism [ 15 ]. These enzymes participate in: the formation of sulfane sulfur-containing compounds (TST, MPST, CTH) [ 16 ]; hydrogen sulfide (H 2 S) production (MPST, CTH, CBS) [ 17 , 18 , 19 ]; protection against oxidative stress (MPST, TST) [ 20 , 21 ]; mitochondrial bioenergetics (TST, MPST) [ 22 , 23 ]; glucose and lipid metabolism (MPST, TST) [ 24 , 25 ]; and cyanide detoxification (TST, MPST, CTH) [ 25 , 26 ]. Abe and Kimura [ 17 ] for the first time reported that H 2 S, which is produced in the brain largely by CBS, may also function as an endogenous neuromodulator.…”
Section: Introductionmentioning
confidence: 99%
“…All of these functions are summarized in the Figure 3 . The persulfide intermediate (ES form) of the enzyme acts as a sulfur-carrier and plays a critical role in sulfur trafficking by delivering sulfur in a “safe” chemical species in several biosynthetic pathways [ 65 , 66 , 67 ]. TST is able to interact with enzymes of oxidative metabolism, such as succinate dehydrogenase [ 64 ], NADH dehydrogenase [ 68 ], xanthine oxidase [ 69 ] and NADH nitrate reductase [ 8 ].…”
Section: Structure and Function Of Tstmentioning
confidence: 99%